Smuts and Mandela: The men who made South Africa - Young, Gordon (New Agenda: SA Journal of Social and Economic Policy, 2025)
Roger Southall has written two-and-a-half good books in one. The first is a study of character, placing the two foremost South African statesmen of the 20th century in counterpoint to each other as it were. So we are shown the many unexpected similarities and resonances in their lives, as well as the great differences between the two men and their work. It is not as if there is a shortage of biographies of these two men: over 30 in the case of Smuts, and seven or eight so far in the case of Mandela. Smuts does of course have the advantage of the semi-official full two-volume treatment by a serious historian, Sir Keith Hancock, which Mandela still awaits. Southall brings the two men together in a single treatment and it is illuminating.